Identification of the genes encoding the catalytic steps corresponding to LRA4 (l‐2‐keto‐3‐deoxyrhamnonate aldolase) and l‐lactaldehyde dehydrogenase in Aspergillus nidulans: evidence for involvement of the loci AN9425/lraD and AN0544/aldA in the l‐rhamnose catabolic pathway. (14th March 2021) - MacCabe, Andrew; Sanmartín, Gemma; Orejas, Margarita
Summary: l ‐rhamnose is found in nature mainly as a component of structural plant polysaccharides and can be used as a carbon source by certain microorganisms. Catabolism of this sugar in bacteria, archaea and fungi occurs by two routes involving either phosphorylated or non‐phosphorylated intermediates. Unlike the corresponding pathway in yeasts, the metabolic details of the non‐phosphorylated pathway in filamentous fungi are not fully defined. The first three genes ( lraA, lraB and lraC ) of the non‐phosphorylated pathway in Aspergillus nidulans have recently been studied revealing dependence on lraA function for growth on l ‐rhamnose and α‐l ‐rhamnosidase production. In the present work, two genes encoding the subsequent steps catalysed by l ‐2‐keto‐3‐deoxyrhamnonate (l ‐KDR) aldolase (AN9425) and l ‐lactaldehyde dehydrogenase (AN0554) are identified. Loss‐of‐function mutations cause adverse growth effects on l ‐rhamnose. Akin to genes lraA‐C and those encoding rhamnosidases ( rhaA, rhaE ), their expression is induced on l ‐rhamnose via the transcriptional activator RhaR. Interestingly, the aldolase belongs to the ftablamily of bacterial l ‐KDR aldolases (PF03328/COG3836) and not that of yeasts (PF00701/COG0329). In addition, AN0554 corresponds to the previously characterized aldA gene (encodes aldehyde dehydrogenase involved in ethanol utilization) thus revealing a previously unknown role for this gene in the catabolism of l ‐rhamnose.